Legal Regulation and Enforcement of International Commercial Contracts in the Context of Digital Technologies (International Journal of Scientific Trends, 2026)
The article examines the theoretical and practical aspects of the legal regulation and enforcement of international commercial contracts in the context of the digitalization of the economy. It analyzes modern approaches to electronic and smart contracts, as well as issues related to their legal recognition, enforcement, and protection of the rights of the parties involved. Particular attention is paid to international standards and national legislation governing the use of digital technologies in commercial activities.